PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN EDUKASI BERBASIS ANDROID PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS XI SMA/MA - Ashuri Yahya; Rasuane Noor; Handoko Santoso (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
This study aimed to develop an Android-based educational game media on the human digestive system material that was suitable for use in the learning process at school. This study used research and development using the four-D development model. The stages carried out were define, design development, and disseminate The results of the study indicated that the development of this media was feasible to be used as teaching materials in schools. The developed product had been validated by a material expert who got an average score of 4.6 and a percentage score of 91. The results of the material expert validation show that the product is very well used for learning. The product developed had been validated by a design expert who got an average score of 4.6 and a percentage score of 91. The results of the validation of the design expert stated that the product was very well used for learning. The trial was conducted on 15 students of class XI at SMA Negeri 5 Metro who were randomly selected. The overall average of the small group trials was 4.6 and the percentage value was 92. The results showed that the product is very good and students were very happy to learn to use teaching materials for Android-based educational game media